2021
DOI: 10.3389/fpsyg.2021.589615
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Fear of COVID-19 and Online Aggressive Behavior: A Moderated Mediation Model

Abstract: Amid the COVID-19 pandemic, fear has run rampant across the globe. To curb the spread of the virus, several governments have taken measures to drastically transition businesses, work, and schooling to virtual settings. While such transitions are warranted and well-intended, these measures may come with unforeseen consequences. Namely, one’s fear of COVID-19 may more readily manifest as aggressive behaviors in an otherwise incognito virtual social ecology. In the current research, a moderated mediation model ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 74 publications
3
26
0
Order By: Relevance
“…In line with this hypothesis, Ye et al (2021) found an increase of online aggressive behavior associated with fear about contagion with COVID-19. In 2016, during an epidemic of the Middle East Respiratory Syndrome (MERS), Jeong et al (2016) examined the effects of a 2-week isolation period on anger and anxiety, and found about 16% of participants experienced anger when isolated due to MERS virus exposure.…”
Section: Introductionsupporting
confidence: 73%
“…In line with this hypothesis, Ye et al (2021) found an increase of online aggressive behavior associated with fear about contagion with COVID-19. In 2016, during an epidemic of the Middle East Respiratory Syndrome (MERS), Jeong et al (2016) examined the effects of a 2-week isolation period on anger and anxiety, and found about 16% of participants experienced anger when isolated due to MERS virus exposure.…”
Section: Introductionsupporting
confidence: 73%
“…Family cohesion is an important protective factor which is negatively related to negative emotion (26)(27)(28)(29). As expected, the study during the COVID-19 epidemic period also has found a significant negative relationship between family cohesion and fear of COVID-19 (30). In families with a high level of cohesion, harmonious family communication can convey a sense of support and security, which can help individuals ease their fear of strange things (31).…”
Section: Fear Of Covid-19 As a Mediatormentioning
confidence: 85%
“…Higher scores indicate a higher level of fear of COVID-19. Good reliability and validity of the fear of the COVID-19 scale have been proved among Chinese participants (30). Confirmatory factor analysis (CFA) suggested that the model fit the data well: CFI = 0.994, TLI = 0.990, RMSEA = 0.038, 90%CI = [0.026, 0.049], SRMR = 0.019.…”
Section: Fear Of Covid-19mentioning
confidence: 95%
See 1 more Smart Citation
“…In conclusion, the increased sense of fear could cause an expression of aggression in the form of anger and hostility among women, while among men, it could mainly be expressed by physical aggression. It is worth emphasizing that there are studies pointing to the relationship between the COVID-19 pandemic and an increased amount of aggressive behaviour on the Internet [ 41 ]. Another study also found an increase in the level of aggression in society during the lockdown caused by the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%